Eye Care Industry Analysis - Pathipati, Akhilesh S.; Tsai, James C. (Journal of Academic Ophthalmology, 2018)
Eye care is a large and growing industry in the United States. Demographic and lifestyle trends will spur increased demand in coming years, but industry earnings will depend on the state of regulation and health care reform. Ophthalmologists and optometrists are the two major service providers in the industry. While the markets for both professions are currently fragmented, the wave of consolidation and commoditization in health care will likely catch up to eye care in coming years. Scope of practice legislation continues to be a topic of heated debate. As it evolves, consolidated practices will move toward an integrated model that uses both types of providers to meet demand.
Keywords: ophthalmology; eye care; industry analysis; health care reform